The START technique - Ramelet, Anne-Sylvie (2012)
Aims: Sclerotherapy is the treatment of choice for telangiectasia of the lower limbs, after elimination of the perforating feeding veins. However, telangiectasia may be refractory to even well-managed treatment, and treatment may be impossible in patients who are extremely sensitive to pain. We propose here a new approach for such cases, the START technique (Sclerotherapy in Tumescent Anaesthesia of Reticular veins and Telangiectasias). Methods: External compression (stockings, bandages) increases the response rate in sclerotherapy for telangiectasia and reticular veins. Nonetheless, the effect of compression on telangiectasia is feeble, even non-existent, in particular in the thigh. During phlebectomy performed using tumescent anesthesia, we noticed that telangiectasias responded particularly well to sclerotherapy when performed at the same time. We attributed these good results to «internal» compression, that Is to say intra-tissue pressure induced by the tumescence. For this reason, we inject the Ringer solution (with lldocaine-epinephrine added) into the sub-cutaneous tissue immediately before or after sclerotherapy for telangiectasia that have been refractory to earlier treatments or are profuse. This injection ensures high intra-tissue pressure for at least one hour. Results: Over the last 6 years, more than 300 patients have been treated for refractory telangiectasia, with good results, though adverse side effects are more frequent (thrombus, pigmentation, small foci of necrosis and subsequent scarring). Conclusions: The START technique is effective, but carries a number of risks. It has a place in our therapeutic arsenal for the treatment of refractory or profuse telangiectasia in patients who have been duly informed about the risk of unsightly complications linked to use of the START technique in its present form. START is also indicated in patients who are unable to bear the pain caused by sclerotherapy for telangiectasia.